Imprisoned Bodies, Muted Voices: Female Characters and Patriarchal Control in Claire Keegan’s Small Things Like These - Ulwiyya Farhana; Ruly Indra Darmawan (Universitas Islam Negeri Palopo, 2026)
This study examines the portrayal of the female characters in Claire Keegan's novel Small Things Like These (2021). In particular, the women held within the Magdalene Laundries are represented as marginalized and oppressed characters within patriarchal systems. This study examines how patriarchal control is implemented in the novel through the confinement and silencing of women, employing a qualitative descriptive approach and Feminist Literary Criticism, as proposed by Gilbert and Gubar (2000). Institutional oppression, collective silence, and historical trauma have been investigated in previous studies of Small Things Like These. However, little attention has been paid to how women are portrayed in light of Gilbert and Gubar's ideas of confinement and silencing. The study offers a distinctive feminist perspective by examining the intertwined processes by which patriarchal institutions control women’s lives. The research indicates that the Magdalene Laundries do not offer women independence, self-determination, or the capacity to control their own lives as institutional power consistently overrides individual will. This oppression is reflected in the institutional and social silence that silences the voices of women, the limitation of women’s freedom in the Magdalene Laundries, and the separation of mothers from their children. The research also points out two related mechanisms of patriarchal control. These are physical confinement, restricting women’s autonomy and isolating them from the outside world, and institutional silence, which prevents their experiences from being acknowledged or challenged by the larger society. These mechanisms suggest that the novel’s oppression is reinforced not only by religious and institutional power but also by social attitudes that normalize compliance and discourage resistance. However, the female characters still seek self-determination and dignity, indicating that oppression and resistance coexist within the same social context. These findings shed light on the mechanisms by which patriarchal institutions control the bodies, voices, and identities of women in contemporary literature, as discussed by Gilbert and Gubar's concepts of confinement and silencing. This is a contribution to feminist literary criticism.